Penerapan Teknologi Augmented Reality Untuk Aplikasi Pengukuran Panjang Suatu Objek - Ifannur, Muhammad Taufik; Wibowo, Adityo Permana (Fakultas Teknik Universitas Hamzanwadi, 2024)
Length measurement is an activity to determine the length value of an object, surface, or other object. The measurement process generally requires conventional length measuring tools such as a ruler or ruler, tape measure, or calipers. Length measurements will experience problems when conditions do not allow the use of conventional measuring instruments due to position factors, the size of objects or surfaces that are too large and difficult for one person to reach, or differences in results obtained when measuring using non-standard units which cause uncertainty the measuring value. Augmented Reality is a technology that allows users to see the real world combined with virtual objects without changing the real world as the main environment. This technology also allows the length measurement process to be carried out using virtual objects as measurement markers and provides real-time measurement results without using conventional length measuring instruments. The results obtained are a length measurement application that can run by relying on virtual objects in the form of pointers which are placed as markers and connected by lines to obtain information in the form of the value of the measurement results. With an average accuracy level of 98.03%, this length measurement application can be used as an alternative medium for carrying out the length measurement process.